Genetic trends in the Kenya Highland Maize Breeding Program between 1999 and 2020 - Ligeyo, Dickson O.; Saina, Edward; Awalla, Bornface J.; Sneller, Clay; Chivasa, Walter; Musundire, Lennin; Makumbi, Dan; Mulanya, Mable; Milic, Dragan; Mutiga, Samuel; Lagat, Abraham; Das, Biswanath; et al. (Frontiers in Plant Science, 2024)
Optimization of a breeding program requires assessing and quantifying empirical genetic trends made through past efforts relative to the current breeding strategies, germplasm, technologies, and policy.To establish the genetic trends in the Kenyan Highland Maize Breeding Program (KHMP), a twodecade (1999-2020) historical dataset from the Preliminary Variety Trials (PVT) and Advanced Variety Trials (AVT) was analyzed. A mixed model analysis was used to compute the genetic gains for traits based on the best linear unbiased estimates in the PVT and AVT evaluation stages. A positive significant genetic gain estimate for grain yield of 88 kg ha -1 yr -1 (1.94% year -1 ) and 26 kg ha -1 year -1 (0.42% year -1 ) was recorded for PVT and AVT, respectively. Root lodging, an important agronomic trait in the Kenya highlands, had a desired genetic gain of -2.65% year -1 for AVT. Results showed improvement in resistance to Turcicum Leaf Blight (TLB) with -1.19% and -0.27% year -1 for the PVT and AVT, respectively. Similarly, a significant genetic trend of -0.81% was noted for resistance to Gray Leaf Spot (GLS) in AVT. These findings highlight the good progress made by KHMP in developing adapted maize hybrids for Kenya's highland agroecology. Nevertheless, the study identified significant opportunities for the KHMP to make even greater genetic gains for key traits with introgression of favourable alleles for various traits, implementing a continuous improvement plan including marker-assisted forward breeding, sparse testing, and genomic selection, and doubled haploid technology for line development.